FUNDAMENTAL FACTORS OF BOND RATING REGISTERED IN INDONESIA BOND MARKET DIRECTORY 2008-2012 - Felix .; Agus Zainul Arifin (Journal of Management and Business, 2014)
Investment decision is determined by the quality of the instrument. The quality of Bond as investment instrument is reflected through its rating since it provides signal and information related to the default risk. Bond rating is determined by many factors. Previous researches have shown different conclusion on which factors influence it, therefore further research is needed to be conducted to determine which factors affect it most. The objective of this research is to explain the influence of fundamental factors to the bonds rating listed in Indonesia Bond Market Directory 2008 – 2012,rated by Pefindo. The samples were tested by the Logistic Regression (Stepwise - Backward). The research concluded that only Retained Earnings, Leverage, and Guarantee have effect on the Bonds Rating.